XCR1+ DCs are critical for T cell-mediated immunotherapy of chronic viral infections - Domenjo-Vila, Eva; Casella, Valentina; Iwabuchi, Ryutaro; Fossum, Even; Pedragosa, Mireia; Castellví, Quim; Cebollada Rica, Paula; Kaisho, Tsuneyasu; Terahara, Kazutaka; Bocharov, Gennady; Argilaguet, Jordi; Meyerhans, Andreas (Cell reports (Cambridge), 2023)
The contribution of cross-presenting XCR1+ dendritic cells (DCs) and SIRPα+ DCs in maintaining T cell function during exhaustion and immunotherapeutic interventions of chronic infections remains poorly characterized. Using the mouse model of chronic LCMV infection, we found that XCR1+ DCs are more resistant to infection and highly activated compared with SIRPα+ DCs. Exploiting XCR1+ DCs via Flt3L-mediated expansion or XCR1-targeted vaccination notably reinvigorates CD8+ T cells and improves virus control. Upon PD-L1 blockade, XCR1+ DCs are not required for the proliferative burst of progenitor exhausted CD8+ T (TPEX) cells but are indispensable to sustain the functionality of exhausted CD8+ T (TEX) cells. Combining anti-PD-L1 therapy with increased frequency of XCR1+ DCs improves functionality of TPEX and TEX subsets, while increase of SIRPα+ DCs dampened their proliferation. Together, this demonstrates that XCR1+ DCs are crucial for the success of checkpoint inhibitor-based therapies through differential activation of exhausted CD8+ T cell subsets. [Display omitted] •XCR1+ DCs are more functional and less prone to LCMV infection than SIRPα+ DCs•Expanding XCR1+ DCs via Flt3L or delivering XCR1-targeting Ag improve virus control•Anti-PD-L1 treatment increases XCR1+ DC numbers and IL-12 production•XCR1+ DCs promote TEX functionality but are dispensable for TPEX proliferation burst Domenjo-Vila et al. show that XCR1+ DCs are crucial in augmenting exhausted CD8+ T cell effector functions during immunotherapeutic interventions in chronic virus infections. Increased T cell functionality leads to reduced virus loads. XCR1+ DCs should be among the preferential targets in immunotherapeutic cure strategies.